IoT Based Poultry Cage Quality Monitoring System - Farida Arinie Soelistianto; Argo Indrianto; Abdullah Anshori; Nur Rizza (West Science Interdisciplinary Studies, 2024)
This research aims to create a better cage quality monitoring system in poultry farms, the parameters observed in particular are ammonia gas, where this gas greatly affects the health and productivity of laying hens, the data taken is processed in percentage terms and a comparison of several conditions in the location where the equipment is placed. The system is made using ESP32 microcontroller as the main board, DHT22 as a temperature and humidity sensor, MQ135 as a sensor to detect ammonia gas levels, GY302/BH1750 as a light sensor, light sensor or light meter sensor is used to optimize the circadian cycle of laying hens, the monitor system uses data sent by the main board to the database and taken as output by the mobile application. At the implementation stage, the system is able to function properly where the monitor system can send and receive data with the database as an intermediary between hardware and software. The DHT22 sensor can detect temperature and humidity changes with minimal error, the error rate obtained for DHT22 sensor reaches 2.26%, the MQ135 sensor can detect ammonia gas levels according to set program, the GY302/BH1750 sensor can detect changes in light with quite optimal accuracy, all sensor activities can be monitored through the software that has been created, when the system is used for a long period of time periodically the main board will stop sending data to the database, This can last 30 to 40 minutes, with a reboot solution.